Adoption of an Electronic Medical Record Tool for Childhood Obesity by Primary Care Providers - Williams, Amy; Turer, Christy; Smith, Jamie; Nievera, Isabelle; McCulloch, Laura; Wareg, Nuha; Clary, Megan; Rajagopalan, Anuradha; Brownson, Ross C.; Koopman, Richelle J.; Hampl, Sarah (Applied Clinical Informatics, 2020)
Background Primary care providers are tasked with the increasingly difficult job of addressing childhood obesity during clinic visits. Electronic medical record (EMR)-enabled decision-support tools may aid providers in this task; however, information is needed regarding whether providers perceive such tools to be useful for addressing nutrition and physical activity lifestyle behaviors.Objectives This study aimed to evaluate the usefulness and usability of FitTastic, an EMR-enabled tool to support prevention and management of childhood obesity in primary care.Methods In this mixed-method study, we implemented the FitTastic tool in two primary-care clinics, then surveyed and conducted focused interviews with providers. Validated Technology Acceptance Model perceived usefulness and National Aeronautics and Space Administration (NASA) perceived usability survey questions were e-mailed to 60 providers. In-depth provider interviews with family medicine and pediatric physicians (n = 12) were used to further probe adoption of FitTastic.Results Surveys were completed by 73% of providers (n = 44). The mean score for FitTastic's usefulness was 3.3 (standard deviation [SD] = 0.54, scale 1–5, where 5 is strongly agree) and usability, 4.8 (SD = 0.86, scale 1–7, where 7 is strongly agree). Usefulness and usability scores were associated with intention to use FitTastic (correlation for both, p < 0.05). Data from provider interviews indicated that useful features of FitTastic included: standardizing the approach to childhood obesity, and facilitating conversations about weight management, without increasing cognitive workload. However, use of FitTastic required more time from nurses to input lifestyle data.Conclusion FitTastic is perceived as a useful and usable EMR-based lifestyle behavior tool that standardizes, facilitates, and streamlines healthy lifestyle conversations with families. Perceived usability and usefulness scores correlated with provider intention-to-use the technology. These data suggest that EMR-based child obesity prevention and management tools can be feasible to use in the clinic setting, with potential for scalability. Usefulness can be optimized by limiting amount of time needed by staff to input data.
Keywords: electronic health records and systems; infants and children; ambulatory care/primary care; adoption; implementation and deployment